Synthesis of Eu3+-doped ZnO/Zn2SiO4 composite phosphor for potent optoelectronic applications - Jaafar, Suhail Huzaifa; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Yaakob, Yazid; Mohd Mustapha, Haslinawati (Springer, 2022)
Eu3+-doped Zn2SiO4/ZnO phosphor-based composites were prepared using a simple thermal treatment method. The effect of Eu3+ content on the morphological and photoluminescence performance was examined using XRD, FTIR, FESEM, UV–Vis, and PL measurement. The existence of two crystal phases by the XRD measurement confirmed the development of zincite (ZnO) and zinc silicate (Zn2SiO4) crystal phases. Besides, the FTIR spectra and FESEM micrograph support the XRD result by verifying ZnO and Zn2SiO4 phase formation through the existence of their characteristic Zn–O–Si and Zn–O vibration modes with the decrement of SiO4 broad absorption band as the Eu3+ concentration increased. Also, UV–Vis absorption spectra presented by the composite samples displayed a broad absorbance that confirmed the addition of Eu3+ ions in the ZnO/Zn2SiO4 has caused the absorption edge of the curve having red shift. The photoluminescence spectrum showed red shift light emissions at 485 and 615 nm, associating with the Zn2SiO4 crystal phase, in addition to the ZnO crystal phase. From the interesting results achieved, this ZnO/Zn2SiO4 phosphor-based composite material can be a potent candidate in optoelectronic applications.